Emotional Quotient, Responsibility and Prosocial Behavior of Junior High School Students at Vijitwittaya School, Watthana District in Bangkok - Thongmoo, Kannapa; Wongkumsin , Theerapat (Mahachula Academic Journal, 2026)
The objectives of this research were to: 1) study the levels of emotional quotient, responsibility and prosocial behavior of students, 2) compare prosocial behavior of students by personal factors, 3) study the relationship between emotional quotient and prosocial behavior of students and 4) study the relationship between responsibility and prosocial behavior of students. The samples consisted of 143 of junior high school students at Vijitwittaya school, Watthana district in Bangkok. Data were collected using questionnaires, and statistical analysis included percentage, mean, standard deviation, t-test, F-test, Least Significant Difference (LSD) and Pearson’s correlation coefficient. The statistical significance were set at .05 and .01 level of confidence. The results as follow: (1) emotional quotient, social responsibility and prosocial behavior of students were at the relatively high level, whereas personal responsibility of students were at the moderate level, (2) students who were different in gender and education level had different prosocial behavior with statistical significance at .01 level, whereas those with different participation in activities had different prosocial behavior with statistical significance at .05 level, (3) emotional quotient was positively related with prosocial behavior of students at .01 level of significance, and (4) responsibility was positively related with prosocial behavior of students at .01 level of significance.